2019
DOI: 10.1007/s10068-019-00628-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential health benefits of phenolic compounds in grape processing by-products

Abstract: Prevention emerges as a powerful approach in minimizing the risk of deleterious lifestyle diseases because therapies do not necessarily guarantee a permanent cure. Accordingly, consumers' growing preference for natural and health-promoting dietary options that are rich in antioxidants has become widespread. Grape (Vitis vinifera) is an antioxidant-rich fruit extensively grown for fresh or processed consumption. The long-term consumption of its polyphenolic antioxidants may promote multiple health benefits. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 80 publications
0
49
0
10
Order By: Relevance
“…Grape pomace accounts for ~25%-35% of the total weight of processed grapes; it contains significant amounts of dietary fiber, for which it may partially replace the forage portion in ruminants' diet [22,37]. Far more interesting, GP is enriched with potent bioactive compounds, especially polyphenols (~2%-6.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grape pomace accounts for ~25%-35% of the total weight of processed grapes; it contains significant amounts of dietary fiber, for which it may partially replace the forage portion in ruminants' diet [22,37]. Far more interesting, GP is enriched with potent bioactive compounds, especially polyphenols (~2%-6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study was to examine the transcriptomic signature of a long-term dietary GP supplementation in dairy cows and to evaluate whether this signature reflects known GP-associated potential health benefits [37]. The main finding was that a 60-day dietary GP supplementation can modulate the expression of a considerable, albeit less than expected, number of genes in dairy cows and induce a noticeable transcriptomic signature that mainly reflects a GP-induced immunomodulatory effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main representatives of polyphenolic compounds in this byproduct are anthocyanins (only in red grape pomaces), catechins, flavonol glycosides, phenolic acids, and alcohols [31]. Together with dietary fibers, phenolic compounds are the most valuable compounds of grape pomace with health beneficial properties, such as the maintenance of intestinal health and the prevention of chronic diseases and cancer [9,32]. Many studies showed the great antioxidant potential of polyphenols and their use in food preservation due to the inhibition of lipid oxidation and antibacterial effect [33].…”
Section: Compoundsmentioning
confidence: 99%
“…According to current research results, grape stem extracts possess important biological activities with multiple benefits for human health due to antioxidant and anti-inflammatory properties [ 5 , 7 , 8 , 9 , 10 , 11 ]. Veskoukis et al [ 10 ] found that this by-product is particularly rich in flavonoids and stilbenes, such as trans -resveratrol and viniferin, which are found in considerably high concentrations.…”
Section: Introductionmentioning
confidence: 99%